2001
DOI: 10.4049/jimmunol.167.3.1592
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Mutation of TNF Receptor I Rescues the RelA-Deficient Mouse and Reveals a Critical Role for NF-κB in Leukocyte Recruitment

Abstract: NF-κB binding sites are present in the promoter regions of many acute phase and inflammatory response genes, suggesting that NF-κB plays an important role in the initiation of innate immune responses. However, targeted mutations of the various NF-κB family members have yet to identify members responsible for this critical role. RelA-deficient mice die on embryonic day 15 from TNF-α-induced liver degeneration. To investigate the importance of RelA in innate immunity, we genetically suppressed this embryonic let… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
194
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(204 citation statements)
references
References 57 publications
10
194
0
Order By: Relevance
“…Thus, rela À/À /tnfr1 À/À double knockout mice have increased susceptibility to bacterial infection (Alcamo et al, 2001). Likewise, B cells from p50 À/À mice do not respond efficiently to LPS, emphasizing the importance of p50-containing complexes, that is, p50/RelA, p50/ p50/BCL-3 and p50/c-Rel, in TLR signaling .…”
Section: Immediate Antimicrobial Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, rela À/À /tnfr1 À/À double knockout mice have increased susceptibility to bacterial infection (Alcamo et al, 2001). Likewise, B cells from p50 À/À mice do not respond efficiently to LPS, emphasizing the importance of p50-containing complexes, that is, p50/RelA, p50/ p50/BCL-3 and p50/c-Rel, in TLR signaling .…”
Section: Immediate Antimicrobial Responsesmentioning
confidence: 99%
“…NF-kB regulates the expression of adhesion molecules, both on leukocytes and endothelial cells, which allow the extravasation of leukocytes from the circulation to the site of infection (Eck et al, 1993). Indeed, RelA-deficient mice display a severe defect in the recruitment of circulating leukocytes to sites of inflammation (Alcamo et al, 2001).…”
Section: Inflammationmentioning
confidence: 99%
“…Initially, the embryonic lethality of rela -/-mice due to massive hepatocyte apoptosis (Beg et al, 1995) revealed a novel function of RelA:p50 as an anti-apoptotic regulator but presented obstacles for genetically assessing RelA's function in the immune system. When the lethality was rescued upon combined inactivation of the gene encoding TNFR1, the resulting rela -/-tnfr1 -/-mice showed an increased susceptibility to bacterial infection and succumbed to neonatal death (Alcamo et al, 2001). Radiation chimeras that were reconstituted with RelA/ TNFR1 deficient hematopoietic cells, also indicated a role for RelA in mounting immune responses.…”
Section: Mouse Genetics Indicate Diverse Canonical Nf-κb Functions Inmentioning
confidence: 99%
“…Moreover, embryonic lethality observed in RelA-/-mice also occurs in mice deficient in IKKβ or IKKγ [82,122]. The insult leading to liver apoptosis was shown to be TNF-α signaling in the developing liver, as crossing RelA-/-mice with either TNFα-/-or TNFR-/-mice rescued this liver phenotype [1,32]. Although TNF-α activates caspases responsible for the initiation and execution of apoptosis, the concurrent activation of NF-κB abrogates TNF-α's pro-apoptotic activity, because NF-κB also targets genes coding for inhibitors of caspase activation and apoptosis.…”
Section: Nf-κb and The Regulation Of Apoptosismentioning
confidence: 99%